Pediatric ambulatory catheter-associated urinary tract infections (CAUTIs): Incidence, risk factors, and patient outcomes. (5th August 2020) - Rinke, Michael L.; Oyeku, Suzette O.; Heo, Moonseong; Saiman, Lisa; Zachariah, Philip; Rosenberg, Rebecca E.; DeLaMora, Patricia; Rabin, Barbara; Mirhaji, Parsa; Klein, Elizabeth; Ford, William J. H.; Obaro-Best, Oghale; et al.
Abstract: Objective: Catheter-associated urinary tract infections (CAUTIs) occur frequently in pediatric inpatients, and they are associated with increased morbidity and cost. Few studies have investigated ambulatory CAUTIs, despite at-risk children utilizing home urinary catheterization. This retrospective cohort and case-control study determined incidence, risk factors, and outcomes of pediatric patients with ambulatory CAUTI. Design: Broad electronic queries identified potential patients with ambulatory urinary catheters, and direct chart review confirmed catheters and adjudicated whether ambulatory CAUTI occurred. CAUTI definitions included clean intermittent catheterization (CIC). Our matched case-control analysis assessed risk factors. Setting: Five urban, academic medical centers, part of the New York City Clinical Data Research Network. Patients: Potential patients were age <22 years who were seen between October 2010 and September 2015. Results: In total, 3, 598 eligible patients were identified; 359 of these used ambulatory catheterization (representing186, 616 ambulatory catheter days). Of these, 63 patients (18%) experienced 95 ambulatory CAUTIs. The overall ambulatory CAUTI incidence was 0.51 infections per 1, 000 catheter days (1.35 for indwelling catheters and 0.47 for CIC; incidence rate ratio, 2.88). Patients with nonprivate medical insurance (odds ratio, 2.5; 95% confidence interval, 1.1–6.3) were significantly more likely to have ambulatory CAUTIs in bivariate models but not multivariable models. Also, 45% of ambulatory CAUTI resulted in hospitalization (median duration, 3 days); 5% resulted in intensive care admission; 47% underwent imaging; and 88% were treated with antibiotics. Conclusions: Pediatric ambulatory CAUTIs occur in 18% of patients with catheters; they are associated with morbidity and healthcare utilization. Ambulatory indwelling catheter CAUTI incidence exceeded national inpatient incidence. Future quality improvement research to reduce these harmful infections is warranted.